Do Socioeconomic Disparities Matter? Unraveling the Impacts of Online Vaccine Misinformation on Vaccination Intention During the COVID-19 Pandemic in China. Issue 2 (1st February 2023) - Lu, Jiahui; Xiao, Yi
Abstract : Concerns have been raised about whether and how groups at high risk of COVID-19 are more likely affected by online vaccine misinformation during the pandemic. This study examined the associations between exposure to online vaccine misinformation and vaccination intention through vaccination perceptions and investigated the moderating role of individuals' socioeconomic status. eHealth literacy was also investigated as a protective factor that mediated the effect of socioeconomic status. A survey of 1, 700 Chinese netizens revealed that increased exposure to online COVID-19 vaccine misinformation predicted lower vaccination intention, which was mediated by negative attitudes, lowered subjective norms, lowered perceived benefits, and higher perceived barriers toward vaccination. Socio-economic status (i.e. education, income, and residence), in general, did not guarantee individuals against the negative impacts of vaccine misinformation. eHealth literacy is critical in reducing susceptibility to vaccine misinformation during the COVID-19 pandemic.